Repeated Ovum Pick-Up and In-vitro Embryo Production in Buffalo - C. Yang (Italian Journal of Animal Science, 2010)
Transvaginal ultrasound-guided ovum pick-up (OPU) was performed on 40 Nili-Ravi and Murrah buffaloes for consecutive 3 times each, at an interval of 3 days. A total of 936 follicles were aspirated, 643 oocytes were retrieved and 456 oocytes of them were usable. The recovery rate was 68.77% (643/935) and the percentage of usable oocytes was 70.92% (456/643), with an average of 3.80±0.23 oocytes usable per buffalo. The number of usable oocytes for the first, second and third OPU was 3.82±0.50;3.82±0.35; 4.05±0.43, respectively, and the difference among them was not significant (P<0.05). After in-vitro maturation (IVM), in-vitro fertilization (IVF) and co-incubation with single layer of granular cells, the cleavage rate was 56.36% - 257/456, blastocyst formation rate was 20.39% (93/456) The result proved the feasibility of consecutive OPU at an interval of 3d and produce buffalo embryo via OPU-IVF. Further studies are needed to improve the efficiency of OPU-IVF.